Body Mass Index in 1.9 Million Adolescents and Stroke in Young Adulthood. Issue 6 (13th May 2021) - Bardugo, Aya; Fishman, Boris; Libruder, Carmit; Tanne, David; Ram, Amit; Hershkovitz, Yael; Zucker, Inbar; Furer, Ariel; Gilon, Roy; Chodick, Gabriel; Tiosano, Shmuel; Derazne, Estela; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: There is a continuous rise in the prevalence of adolescent obesity and incidence of stroke among young adults in many Western countries, but the association between them is unclear. Methods: A nationwide population-based study of 1 900 384 Israeli adolescents (58% men; mean age, 17.3 years) who were evaluated before mandatory military service during 1985 and 2013. Body mass index was classified according to the US Center for Disease Control and Prevention percentiles. Primary outcome was a first stroke event as recorded by the Israeli National Stroke Registry between 2014 and 2018. Cox proportional hazard models were applied. Results: There were 1088 first stroke events (921 ischemic and 167 hemorrhagic; mean diagnosis age, 41.0 years). Adolescent body mass index was significantly associated with a graded increase in the risk for any stroke, ischemic stroke, but less so with hemorrhagic stroke. The hazard ratios for the first ischemic stroke event were 1.4 (95% CI, 1.2–1.6), 2.0 (95% CI, 1.6–2.4), and 3.4 (95% CI, 2.7–4.3) for the 50th to 84th percentile, overweight and obese groups, respectively, after adjustment for sex, age, and sociodemographic confounders with the 5th to 49th body mass index percentile group as the reference. The respective hazard ratios after further adjustment for diabetes status were 1.3 (1.1–1.5), 1.6 (1.3–2.0), and 2.4 (1.9–3.1). Results persisted when the cohort was divided by diabetes status and when ischemic stroke before age 30 was the outcome. Conclusions: High adolescent body mass index was associated with ischemic stroke in young adults with or without diabetes. The rising prevalence of adolescent obesity may increase the future burden of stroke in young adults.